Esther - Macchi, Jean-Daniel (International exegetical commentary on the Old Testament (IECOT), 2018)
Textual forms and editorial stages -- Historical and intellectual context of the book's production -- Literary and thematic characteristics developed in Esther's masoretic form -- Literary and thematic characteristics of other textual forms of Esther -- Perspectives on space and time -- Canonization, use, and reception of the work -- How to use this commentary on Esther's masoretic form -- The fall of Queen Vashti -- Esther's accession and royal installation -- Haman's plot -- Mordecai solicits Esther's help -- Haman's honors -- Mordecai's honors -- The death of Haman -- Triumph, massacre, and festivities.